Implementation of Balanced Nutrition Literacy in Vulnerable Groups in the Community Health Centre (Puskesmas) Cipadu Work Area - Sadiah Multi Karina; Trina Astuti; Iskari Ngadiati; Syarief Darmawan; Lorenta Marpaung; Sarah Afifah (LPPM Universitas Muhammadiyah Tasikmalaya, 2023)
Nutrition is one of the factors in the rate of adequate growth and development. Balanced nutritional needs are needed to maintain and maintain health for mothers and children. The purpose of community service activities is to increase the knowledge of pregnant, and lactating women, and mothers who have children aged 6-24 months. The methods used are lectures, Focus Group Discussions (FGD), and cooking demonstrations. With a total of 8 respondents consisting of 3 pregnant women, 3 breastfeeding mothers, and 2 mothers under five in the Cipadu Health Center area. This activity begins with three stages, namely the preparation, implementation, and evaluation stages. The results of the activity, it was carried out well because it could determine whether parents understood the nutrients for pregnant and lactating women and the provision of good and correct complementary feeding. This service can show a change in behavior and an increase in young mothers’ knowledge about nutrition for pregnant and lactating women and the provision of complementary feeding